Mycobacterium tuberculosis Rv0560c is not essential for growth in vitro or in macrophages. (January 2017) - Kokoczka, Rachel; Schuessler, Dorothée L.; Early, Julie V.; Parish, Tanya
Abstract: Mycobacterium tuberculosis Rv0560c, a putative benzoquinone methyl transferase, is heavily induced in response to salicylate exposure. It has some similarity to Escherichia coli UbiG, although its role in ubiquinone or menaquinone synthesis is not clear, since M. tuberculosis is not known to produce ubiquinone. We constructed an unmarked in-frame deletion of Rv0560c in M. tuberculosis to determine its role in vitro . Deletion of Rv0560c in M. tuberculosis had no effect on growth in medium containing salicylate or in its ability to grow in macrophages. In addition, no change to compound sensitivity, as determined by minimum inhibitory concentrations, for a range of compounds targeting respiration was noted. Plumbagin, ethambutol and CCCP had the same minimum bactericidal concentration against the deletion and wild-type strains. Taken together these data show that Rv0560c is dispensable under in vitro conditions in both axenic and macrophage culture and suggest that the role of Rv0560c may be in an alternate biosynthetic pathway of menaquinone which is only used under specific growth conditions.